2021
DOI: 10.2196/28999
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Data Mining Techniques (Decision Tree Models) for Examining the Impact of Internet-Based Cognitive Behavioral Therapy for Tinnitus: Machine Learning Approach

Abstract: Background There is huge variability in the way that individuals with tinnitus respond to interventions. These experiential variations, together with a range of associated etiologies, contribute to tinnitus being a highly heterogeneous condition. Despite this heterogeneity, a “one size fits all” approach is taken when making management recommendations. Although there are various management approaches, not all are equally effective. Psychological approaches such as cognitive behavioral therapy have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…This indicates that overfitting is a common problem arising in small data sets 42 . In contrast, DT, XGBoost, and NB methods have exhibited better performance in other studies 43 45 , which however did not assess calibration. A recent systematic review 28 did not find an incremental value of flexible ML techniques over traditional statistical methods in relatively small data sets (median sample size: 1250); moreover, calibration was not addressed in 79% of ML studies.…”
Section: Discussionmentioning
confidence: 80%
“…This indicates that overfitting is a common problem arising in small data sets 42 . In contrast, DT, XGBoost, and NB methods have exhibited better performance in other studies 43 45 , which however did not assess calibration. A recent systematic review 28 did not find an incremental value of flexible ML techniques over traditional statistical methods in relatively small data sets (median sample size: 1250); moreover, calibration was not addressed in 79% of ML studies.…”
Section: Discussionmentioning
confidence: 80%
“…Another study by Seydel et al ( 2013 ) recognized age and gender as the most relevant factors to predict tinnitus distress. Rodrigo et al ( 2021 ) investigated the impact of several features for the success of internet-based CBT (cognitive behavioral therapy) on tinnitus patients. In this study, age and gender were used as features but the feature that proved the highest impact on the outcome of the treatment was the education level of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of these trials have been presented in our recent manuscripts [8,9]. Our recent studies from the UK sample have shown that the baseline tinnitus severity (i.e., TFI scores) and also education level was found to be the key prognostic factors of ICBT intervention [20].…”
Section: Discussionmentioning
confidence: 99%